Effectiveness of Papaya Leaf Squeeze (Carica Papaya L.) as a biolarvicide against the larval mortality of mosquito larvae of Tribus Anophelini (Anopheles sp) and Tribus culicini (Aedes sp) - Putri Nurul Afni Kau; Herlina Jusuf; Tri Septian Maksum (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Mosquito-borne diseases are still a public health problem. Mosquitoes of the Anophelini tribe (Anopheles sp) play a role in the transmission of malaria, while the Culicini tribe (Aedes sp) transmits dengue hemorrhagic fever (DHF). One of the safest larval control efforts is the use of biolarviccides, such as papaya plants (Carica papaya L.) which are more friendly to humans and the environment. The purpose of the study was to determine the effectiveness of papaya leaf juice as a biolarvicide against the mortality of Anopheles sp and Aedes sp mosquito larvae. Pseudo-experimental research type, Non-equivalent control group design. Samples of 400 larvae, consisting of 200 larvae of Anopheles sp and 200 larvae of Aedes sp instar III. The larvae were given a concentration of 10%, 20%, and 30% papaya leaves with 3 repetitions, observed for 24 hours. Data analysis was conducted using the One-Way ANOVA test and the Independent Sample t-test. The results of the study were the highest at a concentration of 30% of 90%, the lowest at a concentration of 10% of 40%. The mortality of Aedes sp larvae is highest at a concentration of 30% at 95%, lowest at a concentration of 10% at 50%. In conclusion, there was no difference in the effectiveness of papaya leaf juice as a biolarvicide on the mortality of Anopheles sp and Aedes sp mosquito larvae (p-value = 0.930). The public is advised to use papaya leaf juice biolarvicide, as an alternative to mosquito larval control that is more environmentally friendly.